Helping Students Develop the Critical Awareness about Discrimination in the Eighth Grade Classroom (2017)
ABSTRACT: This action research project explores how the designing and implementation of a critical literacy unit helps students to develop their critical awareness about discrimination in an eighth grade classroom of a female public school in Medellin (Colombia). The information necessary to show the results of the project was obtained through observations, interviews, surveys, and students’ artifacts. After an analysis of the data, they revealed the ways in which students live and face discrimination. Some critical media literacy strategies were used in order to promote students’ critical awareness resulting in a positive change regarding the attitude of the students when facing this social issue.